2005
DOI: 10.1124/jpet.105.095166
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Mapping of Reactive Oxygen Species by in Vivo Electron Spin Resonance Spectroscopy in Indomethacin-Induced Gastric Ulcers in Rats

Abstract: Reactive oxygen species (ROS) are thought to be involved in the gastric ulcer formation induced by indomethacin, a typical nonsteroidal anti-inflammatory drug. However, the location and the time course of ROS generation remain unknown. To assess the sites of ROS generation, we applied the noninvasive measurement of ROS to indomethacin-treated rats. By giving orally a membrane-permeable or impermeable probe, the spectra were collected as a function of time by in vivo 300-MHz electron spin resonance (ESR) spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 39 publications
3
36
0
Order By: Relevance
“…Besides the opportunity to use ESR for analyzing in vivo samples, e.g., by directly coupling it to a microdialysis facility [128], it allows non-invasive imaging, similar to NMR tomography, showing spatially resolved oxidative processes in the body [125,129]. As the ability of a biological system to reduce the introduced spin trap is proportional to its antioxidant activity, the disappearance of the ESR signal can be used as a marker for the condition of the antioxidant defense system.…”
Section: Determination Of H 2 Omentioning
confidence: 99%
“…Besides the opportunity to use ESR for analyzing in vivo samples, e.g., by directly coupling it to a microdialysis facility [128], it allows non-invasive imaging, similar to NMR tomography, showing spatially resolved oxidative processes in the body [125,129]. As the ability of a biological system to reduce the introduced spin trap is proportional to its antioxidant activity, the disappearance of the ESR signal can be used as a marker for the condition of the antioxidant defense system.…”
Section: Determination Of H 2 Omentioning
confidence: 99%
“…Thus, the rate of ESR signal decay of nitroxyl spin probes have been used to monitor free radical production and redox status in various animal models, including tumor inoculated in mouse footpads, 8) indomethacin-induced gastric ulcers, 9) rheumatoid arthritis, 10) hypertension, 11) cerebral ischemia-reperfusion, 12) lung injury caused by diesel exhaust particles, 13) and radiationinduced oxidative injury. 14) Phumala et al 15) have demonstrated in an acute iron overload murine model that free radical production is dependent on the availability of "chelatable iron" present transiently following a single injection of ferric citrate (0.2 µmol/g body weight).…”
mentioning
confidence: 99%
“…Of impressive note was the similar or better cytoprotection exhibited by the microcapsules when compared to the standard reference drug, misoprostol (40 g/kg). Indomethacin possesses pharmacological and toxicological properties primarily due to its inhibition of cyclo-oxygenase isoenzymes responsible for the production of prostaglandins (PGs), promoting haemorrhagic ulceration in rats by oxidative stress and a decline in mucosal production of PG (Utsumi et al, 2006). The protection provided by extract and formulations of Entada africana against Indomethacin induced ulceration, may be suggestive of an enhanced mucosal synthesis or mobilization of PG, consequently protecting gastric mucosa similar to misoprostol, a synthetic prostaglandin analogue.…”
Section: Resultsmentioning
confidence: 98%